1976
DOI: 10.1071/mf9760379
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of some inland surface waters in South, Western and northeren Australia

Abstract: Numerous analyses of the major ions in surface waters of South Australia, south-western Western Australia, and northern Australia are presented and discussed. In South Australia three regions were investigated: the Yorke Peninsula, the Snowtown area, and the extreme south-east including the Coorong. In all three areas salinities were high, except for Lake Alexandrina and Lake Albert at the mouth of the River Murray, and sodium and chloride were the dominant ions. In rivers and standing waters in the south-west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Morton & Bayly (1977), in their study of the ecology of some temporary freshwater pools in Victoria, discussed the presence of ostracods in such habitats and described the seasonality of some of the ostracod species. The taxonomic descriptions of freshwater ostracods from north-western Australia by McKenzie (1966a), supplemented by the physicochemical data of Williams & Buckney (1976) and additional remarks of Williams (1979), for the same localities from which the ostracods had been originally collected, are of interest. Similarly, the descriptions of ostracods from mainly athalassic saline waters from Western Australia and South Australia by McKenzie (1978), supplemented by the same work of Williams & Buckney (1976) for the ostracod localities, are informative on salinity tolerance of some species.…”
Section: Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Morton & Bayly (1977), in their study of the ecology of some temporary freshwater pools in Victoria, discussed the presence of ostracods in such habitats and described the seasonality of some of the ostracod species. The taxonomic descriptions of freshwater ostracods from north-western Australia by McKenzie (1966a), supplemented by the physicochemical data of Williams & Buckney (1976) and additional remarks of Williams (1979), for the same localities from which the ostracods had been originally collected, are of interest. Similarly, the descriptions of ostracods from mainly athalassic saline waters from Western Australia and South Australia by McKenzie (1978), supplemented by the same work of Williams & Buckney (1976) for the ostracod localities, are informative on salinity tolerance of some species.…”
Section: Ecologymentioning
confidence: 99%
“…The taxonomic descriptions of freshwater ostracods from north-western Australia by McKenzie (1966a), supplemented by the physicochemical data of Williams & Buckney (1976) and additional remarks of Williams (1979), for the same localities from which the ostracods had been originally collected, are of interest. Similarly, the descriptions of ostracods from mainly athalassic saline waters from Western Australia and South Australia by McKenzie (1978), supplemented by the same work of Williams & Buckney (1976) for the ostracod localities, are informative on salinity tolerance of some species. In addition, Buckney & Tyler (1976) provided chemical data for two saline localities in central Tasmania from which two species of ostracods were collected.…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic composition of saline lakes in Western Australia reported by Williams & Buckney (1976) and Geddes et a1 (1981) shows the constancy so characteristic of Australian saline lakes and similar to that of sea water. As there is no reason to believe the lakes tested in this study differ, ionic composition is not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, a large number of departures from this pattern occurs, with Mg, Ca, SO, and HCO, + CO, sometimes important in particular lakes. Thus, Chinese and Mongolian salt lakes do not have the ionic homogeneity seen, for example, in Australian salt lakes (Williams & Buckney, 1976); in China, at least, whilst the most frequent pattern of ionic dominance is Na>Mg>K>Ca:Cl>SO,>HCO,+CO,, Mg may dominate the cations in some lakes, and HCO, + CO, the anions in others. Table 7 has been compiled in order to illustrate this ionic variety.…”
Section: Major Chemical Featuresmentioning
confidence: 99%